2019
DOI: 10.1002/jor.24430
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Dependent Cannabidiol‐Induced Elevation of Intracellular Calcium and Apoptosis in Human Articular Chondrocytes

Abstract: Cannabidiol (CBD) is the most abundant non‐psychoactive compound of Cannabis sativa extracts. Cannabinoids have been shown to exhibit anti‐inflammatory, analgesic, antioxidant, neuroprotective, and anti‐tumorigenic effects. In the present study, we investigated the effects of CBD on human articular chondrocytes. Cell viability was determined by Resazurin assays. Apoptosis was analyzed by annexin‐V/7‐actinomycin D (7‐AAD) staining followed by flow cytometry. Caspase 3/7 activity was measured with caspase assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…More detailed research is needed to clarify this effect; however, the inflammatory state is not always negative. In arthritic in vitro studies, CBD promoted chondrocyte and synoviocyte apoptosis but with stronger effects on the inflammatory-activated cells, which may be a positive result that indicates anti-arthritic activity [ 89 , 90 ]. The discussed studies indicate a positive influence of CBD on various diseases; nevertheless, animal studies cannot always be translated into human results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More detailed research is needed to clarify this effect; however, the inflammatory state is not always negative. In arthritic in vitro studies, CBD promoted chondrocyte and synoviocyte apoptosis but with stronger effects on the inflammatory-activated cells, which may be a positive result that indicates anti-arthritic activity [ 89 , 90 ]. The discussed studies indicate a positive influence of CBD on various diseases; nevertheless, animal studies cannot always be translated into human results.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results from the work of Winklmayr et al in an in vitro human chondrocytes culture showed that CBD concentrations greater than 4 μM diminished cell viability and increased caspase 3/7 activity, elevated Ca 2+ and Extracellular signal-regulated kinases 1/2 phosphorylation and enhanced apoptotic cell population. This effect was mediated via the CB1 receptor, since AM251 inhibited Ca 2+ influx and reduced the toxic effects of CBD [ 90 ].…”
Section: The Analgesic Potential Of Cbdmentioning
confidence: 99%
“…Subcultures were established once a week until passage 25. Primary chondrocytes were isolated from total human knee arthroplasty samples with informed consent and ethical approval by the Ethics Committee of Salzburg (415-E/1965/4-2015) as described in Winklmayr et al (2019). In brief, cartilage samples were removed from subchondral bone and crashed into small pieces.…”
Section: Cell Culturementioning
confidence: 99%
“…Cannabis is a well established endocrine disruptor [ 49 59 ]. Whilst there are no extant papers documenting the relationship of cannabinoid exposure to ovarian cancers oocytes have been shown to be highly sensitive to cell death during cell division under the influence of cannabinoids [ 60 ] and the ovary is also known to be highly sensitive to inhibitors of mitochondrial metabolism a role which several cannabinoids including cannabidiol have long been known to play [ 36 , 37 , 61 65 ].…”
Section: Introductionmentioning
confidence: 99%